THE INFLUENCE OF APPLICATION OF “CLEAN VALUE” AND THE EMPOWERMENT OF EMPLOYEE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE AT PT PERTAMINA MARKETING OPERATION REGION V SURABAYA - Moh Alfian; I Gede Arimbawa; Elok Damayanti (Journal of World Conference (JWC), 2019)
This study aims to analyze the effect of applying clean values, employee empowerment towards organizational citizenship behavior with employee performance. This type of research used a quantitative approach. Data collection used interviews, observation and questionnaire dissemination. The population of this research were employees of PT. Pertamina MORV Surabaya with a sample of 135 respondents from 204 employees. The analytical method used the application of SmartPLS (Partial Least Square). Based on the results of the study, it can be concluded clean value management, employee empowerment have a significant effect on organizational citizenship behavior. Clean values, empowerment, organizational citizenship behavior have a significant effect on employee performance.